PERANCANGAN MESIN PENGERING CABAI MERAH PROTOTIPE MENGGUNAKAN TUBULAR HEATER DENGAN KAPASITAS PENGERINGAN 4 KG: Indonesia - Asep Rachmat (J-ENSITEC (Journal of Engineering and Sustainable Technology), 2021)
So far, the drying process carried out by farmers is still simple, namely by drying it directly in the sun. This method is less effective because it will require a large area with a relatively long drying time of 10-12 days. The author will conduct research on the design and testing of a red chili drying machine using Solidwork software. The drying process used in this red chili drying machine uses a tubular heater. It is hoped that the design of this red chili drying machine can increase the production of dry red chilies. The results of the research show that the chili drying machine is designed into 2 parts that are bulkhead using a filter with dimensions of 385 x 320 mm, the dimensions of the drying room are 400 mm long, 421 mm wide, 353 mm high, in the drying room section there are 10 shelves that can be assembled and assembled. with dimensions of 400 x 380 mm for storing chilies to be dried and the dimensions of the combustion chamber having dimensions of 140 mm in length, 421 mm in width and 353 mm in height, then the tool will be made of stainless steel sheet with a thickness of 3 mm. / fan with a diameter of 170 mm which has 5 propeller blades, and the fan is rotated using an electric motor type yj62-25 with a voltage of 100-240 VAC, a frequency of 50/60 HZ and a power of 5-100W.